CAUSES OF THE SECOND WORLD WAR - Saidullaeva Ainura Zhienbai kizi (Western European Studies, 2025)
World War II (1939–1945) was the largest military conflict in human history. The reasons for its outbreak were multifaceted and related to the aftermath of World War I, political, economic and ideological factors. The key causes of the war were the Treaty of Versailles of 1919, which imposed severe restrictions on Germany, the rise of fascist regimes in Europe (Germany, Italy, Japan), the economic crisis of 1929, the aggressive foreign policy of Nazi Germany and its allies, as well as the appeasement policy of Great Britain and France. Hitler's Germany sought to revise borders, expand "living space" and destroy the communist Soviet Union. In 1939, Germany and the USSR signed the Molotov–Ribbentrop Pact, dividing spheres of influence in Eastern Europe. The war began with Germany's attack on Poland on September 1, 1939, after which Great Britain and France declared war on Germany. Thus, the Second World War was caused by a complex of historical reasons, including revanchism, economic crises and the expansionist ambitions of fascist states.
Keywords: World War II; causes; Treaty of Versailles